Cryptic genomic rearrangements in three patients with 46,XY disorders of sex development. - Maki Igarashi (Public Library of Science (PLoS), 2013)
Background 46,XY disorders of sex development (46,XY DSD) are genetically heterogeneous conditions. Recently, a few submicroscopic genomic rearrangements have been reported as novel genetic causes of 46,XY DSD. Methodology/principal findings To clarify the role of cryptic rearrangements in the development of 46,XY DSD, we performed array-based comparative genomic hybridization analysis for 24 genetic males with genital abnormalities. Heterozygous submicroscopic deletions were identified in three cases (cases 1-3). A ∼8.5 Mb terminal deletion at 9p24.1-24.3 was detected in case 1 that presented with complete female-type external genitalia and mental retardation; a ∼2.0 Mb interstitial deletion at 20p13 was identified in case 2 with ambiguous external genitalia and short stature; and a ∼18.0 Mb interstitial deletion at 2q31.1-32 was found in case 3 with ambiguous external genitalia, mental retardation and multiple anomalies. The genital abnormalities of case 1 could be ascribed to gonadal dysgenesis caused by haploinsufficiency of DMRT1, while those of case 3 were possibly associated with perturbed organogenesis due to a deletion of the HOXD cluster. The deletion in case 2 affected 36 genes, none of which have been previously implicated in sex development. Conclusions/significance The results indicate that cryptic genomic rearrangements constitute an important part of the molecular bases of 46,XY DSD and that submicroscopic deletions can lead to various types of 46,XY DSD that occur as components of contiguous gene deletion syndromes. Most importantly, our data provide a novel candidate locus for 46,XY DSD at 20p13.